A Mixing Washer Optimization for Salt Purification - Tjahjono, Endro Wahju; Suwarno, Suwarno; Saputra, Hens; Iskandriawan, Bambang; Syaftika, Novi; Nuswantoro, Dorit Bayu Islami; Dwimansyah, Ridho; Hamzah, Hamzah; Darmawan, Muhammad Arif (Majalah Ilmiah Pengkajian Industri; Journal of Industrial Research and Innovation, 2025)
Conventional salt production from seawater and solar evaporation has the drawback such as contains many impurities of magnesium, calcium and mud. The purification process is necessary to achieve the standard quality requirements for consumption and industrial salt. A simple salt purification process was carried out by using saturated salt solution through a mixing washer. This research focuses on design and optimization of mixing washer. During the washing process, baffles act as flow restrictors, to reduce swirling and encourage vertical fluid circulation. This equipment was mainly used in the mixing and suspension making process of solids using vertical cylindrical tanks where vortexes are easily formed, regardless of the type of impeller. The baffle strength was tested and confirmed using CFD simulation. The result of the wooden baffle was strong enough to be used in the mixing washer with a diameter of 850mm. The optimum mixing washing process was obtained at 200 rpm for 10 minutes. The coarse salt could be increased in purity from 88% NaCl to 98%. Mg content was reduced to 0.7% respectively.